Prediction of post-stenting biomechanics in coarcted aortas: A pilot finite element study. (22nd May 2020) - Caimi, Alessandro; Pasquali, Matteo; Sturla, Francesco; Pluchinotta, Francesca R.; Giugno, Luca; Carminati, Mario; Redaelli, Alberto; Votta, Emiliano
Abstract: Endovascular stenting has recently become a standard treatment for native coarctation of the aorta (CoA) in children and young adults, given the efficacy in relieving vessel obstruction with a low incidence of adverse events. Yet, despite the short-term success of the technique, late hypertension remains an endemic risk. To assess the impact of the percutaneous procedure on the aortic wall biomechanics, we designed a novel finite element (FE) protocol for the simulation of endovascular stenting in three patient-specific CoA anatomies, developing a remeshing procedure that allows for coping with different CoA severities. Our FE protocol was able to yield numerical results on stent distortions and stresses, as well as on changes in aortic wall stresses and distensibility. These results were consistent with intraprocedural in-vivo evidences and with previous findings from the literature, and they suggest that our numerical approach could be used to understand the role of patient specific anatomical features (CoA severity and arch type) on the post-stenting aortic biomechanics. If soundly validated on a vast cohort of patients, our approach could support patient selection for the procedure.